2016
DOI: 10.3390/rs8060504
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Daily Solar Radiation Budget at Kilometer Resolution over the Tibetan Plateau by Integrating MODIS Data Products and a DEM

Abstract: Considering large and complex areas like the Tibetan Plateau, an analysis of the spatial distribution of the solar radiative budget over time not only requires the use of satellite remote sensing data, but also of an algorithm that accounts for strong variations of topography. Therefore, this research aims at developing a method to produce time series of solar radiative fluxes at high temporal and spatial resolution based on observed surface and atmosphere properties and topography. The objective is to account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
2
18
1
Order By: Relevance
“…This is due to the opposite effect of AOD on the global and direct irradiances and diffuse irradiance; a decrease of AOD enhances global and direct irradiances and simultaneously reduces diffuse irradiance. The MODISbased results of global irradiance are similar to those reported by Roupioz et al [47] from the Qomolangma station where they validated the estimated MODIS-based global irradiance using the Yang et al [25] model by integrating MODIS data and a digital elevation model (DEM) over the Tibetan Plateau.…”
Section: Validation Of Downward Sw Radiative Fluxessupporting
confidence: 73%
See 2 more Smart Citations
“…This is due to the opposite effect of AOD on the global and direct irradiances and diffuse irradiance; a decrease of AOD enhances global and direct irradiances and simultaneously reduces diffuse irradiance. The MODISbased results of global irradiance are similar to those reported by Roupioz et al [47] from the Qomolangma station where they validated the estimated MODIS-based global irradiance using the Yang et al [25] model by integrating MODIS data and a digital elevation model (DEM) over the Tibetan Plateau.…”
Section: Validation Of Downward Sw Radiative Fluxessupporting
confidence: 73%
“…Not only the coarse resolution of MODIS AOD, but primarily the MODIS DT algorithm induces errors in the estimated fluxes. It should be noted that the SARA-based scheme obtained smaller or similar RMSE for global irradiance, also compared to other studies by Bisht and Bras [46], Roupioz et al [47], and Rutan et al [38]. Another advantage of the SARA-based scheme, as compared to the MODIS-based scheme and the CERES/SARB data product [38], is that it produces higher-resolution fluxes that are necessary to represent spatial variability throughout a landscape.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…To account for the impact of topography on the spatial distribution of the solar radiative budget, Roupioz et al [17] used the observed surface and atmosphere properties and topography to derive high temporal and spatial resolution solar radiative fluxes over the Tibetan Plateau (i.e., daily at 1 km resolution). The validation showed that, although the solar radiation estimates are satisfying in clear sky conditions, the algorithm is less reliable under cloudy sky conditions.…”
Section: Surface Energy Fluxesmentioning
confidence: 99%
“…The characterization of the temporal and spatial distribution of surface solar irradiance is very challenging due to cloud presence and, in complex orography, to shadowing and altitude/slope effects [1,2]. Clouds play a major role in the Earth-atmosphere system, affecting the incoming solar and outgoing thermal energy with interactions with the other atmospheric components.…”
Section: Introductionmentioning
confidence: 99%